2009
DOI: 10.1021/ac900956y
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Self-Assembled Monolayers for Label-Free and Unamplified Surface Plasmon Resonance Biosensing in Crude Cell Lysate

Abstract: Short peptides, composed of polar or ionic amino acids, derived with a short organic thiol, significantly reduce nonspecific adsorption of proteins in complex biological matrices such as serum and crude cell lysate, which have nonspecific protein concentrations of 76 and 30-60 mg/mL, respectively. Minimizing these nonspecific interactions has allowed rapid and direct quantification of beta-lactamase in a crude cell lysate using a surface plasmon resonance (SPR) biosensor. A library of short peptides with varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
97
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 64 publications
2
97
0
1
Order By: Relevance
“…Recently, to reproduce the chemical and structural complexity of proteins, a nanoengineering approach was used to design peptides able to cap such surfaces, conferring stability [22], minimizing nonspecific interactions [23], and providing an appropriate template to incorporate several molecular receptors or recognition groups [23,24]. Most of these sequences, such as CALNN and 3-MPA-(Ser) 5 -OH (where MPA is mercaptoproprionic acid), are provided by rational or combinatorial designs.…”
Section: Designed Synthetic Peptidesmentioning
confidence: 99%
“…Recently, to reproduce the chemical and structural complexity of proteins, a nanoengineering approach was used to design peptides able to cap such surfaces, conferring stability [22], minimizing nonspecific interactions [23], and providing an appropriate template to incorporate several molecular receptors or recognition groups [23,24]. Most of these sequences, such as CALNN and 3-MPA-(Ser) 5 -OH (where MPA is mercaptoproprionic acid), are provided by rational or combinatorial designs.…”
Section: Designed Synthetic Peptidesmentioning
confidence: 99%
“…For instance, nanoparticles biomimetic interfaces have been employed to immobilize living cells, which allows adsorption based on electrostatic force or weak interaction between nanoparticles and cells membrane [6][7][8][9]. Antibodies, functional peptides, such as arginine-glycine-aspartic acid-serine (RGDS) tetrapeptide, have been used to functionalize electrode for capturing cells via the specific binding between these molecules and cellular surface units [10][11][12][13]. Moreover, aptamer-based interface has also been used for enrichment and detection of multiple cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…10 Concurrently, tethered amino acids, such as phenylalanine, have been shown to be resistant to biofouling. 11 Surface plasmon resonance is a well-established surfacesensitive optical technique which allows for the qualitative and quantitative measurements of biomolecular interactions in real time without requiring a labeling procedure. 12 The excellent sensitivity of SPR for detecting proteins tenders the increasing popularity of SPR in bioanalyses.…”
mentioning
confidence: 99%
“…17,20 PEG-functionalized surfaces reveal good ability for prevention of nonspecific protein adsorption with only 100 ng/cm 2 nonspecific adsorption. 11 However, their applications have been limited by the need for carboxylic acid functionalization of PEG to immobilize the molecular receptor. Bolduc et al demonstrated that nonspecific adsorption can be substantially reduced by functionalizing gold surfaces with 3-mercaptopropionic acid (3-MPA)-linked different amino acids and peptide sequences.…”
mentioning
confidence: 99%